Bis(cyclopropenium)phosphines: Synthesis, Reactivity, and Applications. Issue 43 (16th September 2016) - Mehler, Gerlinde; Linowski, Pawel; Carreras, Javier; Zanardi, Alessandro; Dube, Jonathan W.; Alcarazo, Manuel
Abstract: A straightforward route for the preparation of a set of bis(cyclopropenium)‐substituted phosphines is reported. Due to their dicationic nature, these ligands depict an excellent π‐acceptor character. The effect of the ligand substituent pattern on the catalytic activity of the metal complexes thereof derived is also studied. Whereas sterically demanding biaryl groups directly attached to the phosphorus atom seem to facilitate elementary steps such as the product release from the catalyst, long chain dialkylamino groups on the cyclopropenium units maximize the catalysts solubility and, thus, allow the use of typical apolar solvents such as toluene. Importantly, all new ligands prepared can be easily handled in air. Finally, the impact of the newly prepared dicationic phosphines in hydroarylation reactions is demonstrated. In particular, their use in the synthesis of several naphtho[1, 2‐ b ]furanes and naturally occurring naphthalene derivatives such as Calanquinone C is reported. Abstract : The bulkier the better ! A series of strong π‐acceptor dicationic phosphines were prepared through a modular synthetic route. Preliminary studies on Au catalysis indicate that, once the Lewis acidity on the metal surpasses a critical value, it is the bulkiness of the ligand that controls the overall reaction speed.